Ø·Ø±Ø§Ø¦Ù‚ ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØ© Ù„Ù„Ù†Ø§Ø·Ù‚ÙŠÙ† Ø¨ØºÙŠØ±Ù‡Ø§ Ø§Ù„Ù…Ø³ØªÙ†Ø¨Ø·Ø© Ù…Ù† Ø£ÙÙƒØ§Ø± Ø£ØÙ…Ø¯ ÙØ¤Ø§Ø¯ Ø£ÙÙ†Ø¯ÙŠ - Abul Ma'ali; Uril Bahruddin (Universitas Negeri Semarang, 2022)
Abstract Arabic teaching suffers from the problem of forming students who are proficient in communicative skills, as it is difficult to master, and the reason may be due to the lack of appropriate methods. The objectives of this research are to highlight the teaching methods for developing the communication skills of Indonesian students according to the perspective of Ahmad Fuad Effendi, one of the prominent experts in Arabic teaching in Indonesia. Researchers use qualitative approach by studying the perspective of experts in Arabic teaching. The data was taken from the documents related to the subject, especially the book Methods of Teaching the Arabic Language, and the interview with the author. The data was analyzed according to the theory of Miles, Huberman and Saldana. The results of this research, it is that the teaching methods for developing the communication skills of Indonesian students according to the perspective of Ahmad Fuad Effendi contain three things: (1) the need to benefit from the different language teaching methods, as there is no single method suitable for all circumstances and situations. (2) Emphasis on the communicative aspect in teaching Arabic, because the most important objectives of teaching Arabic are communication. (3) The application of intensive Arabic lessons to teach language skills, where sufficient study hours are available. The conclusion of this research indicated that mastering communication skills can be obtained from the use of various methods with special attention to communicative learning and intensive learning. Keywords: Methods, skill development, communicative, intensive course Ù…Ù„Ø®Øµ Ø§Ù„Ø¨ØØ« ÙŠØ¹Ø§Ù†ÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù…Ù† Ù…Ø´ÙƒÙ„Ø© ØªÙƒÙˆÙŠÙ† Ø§Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…ØªÙ‚Ù†ÙŠÙ† ÙÙŠ Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØ©ØŒ ØÙŠØ« ØµØ¹ÙˆØ¨Ø© Ø¥ØªÙ‚Ø§Ù†Ù‡Ø§ØŒ ÙˆÙ‚Ø¯ ÙŠØ±Ø¬Ø¹ Ø³Ø¨Ø¨Ù‡Ø§ Ø¥Ù„Ù‰ Ø¹Ø¯Ù… ÙˆØ¬ÙˆØ¯ Ø§Ù„Ø·Ø±Ø§Ø¦Ù‚ Ø§Ù„Ù…Ù†Ø§Ø³Ø¨Ø©. ÙˆØ£Ù‡Ø¯Ø§Ù Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¥Ø¨Ø±Ø§Ø² Ø§Ù„Ø·Ø±Ø§Ø¦Ù‚ Ù„ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØ© Ù„Ù„Ø·Ù„Ø¨Ø© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠÙŠÙ† ÙˆÙÙ‚ Ø£ÙÙƒØ§Ø± Ø§Ù„Ø£Ø³ØªØ§Ø° Ø£ØÙ…Ø¯ ÙØ¤Ø§Ø¯ Ø£ÙÙ†Ø¯ÙŠØŒ ÙˆÙ‡Ùˆ Ø£ØØ¯ Ø§Ù„Ø®Ø¨Ø±Ø§Ø¡ Ø§Ù„Ø¨Ø§Ø±Ø²ÙŠÙ† ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø¨Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§. ÙˆÙ…Ø¯Ø®Ù„ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙƒÙŠÙÙŠ Ø¨Ù†ÙˆØ¹ Ø¯Ø±Ø§Ø³Ø© Ø£ÙÙƒØ§Ø± Ø§Ù„Ø®Ø¨Ø±Ø§Ø¡ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. ØªÙ… Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø®Ù„Ø§Ù„ Ø¯Ø±Ø§Ø³Ø© Ø§Ù„ÙˆØ«Ø§Ø¦Ù‚ Ø§Ù„Ù…ØªØ¹Ù„Ù‚Ø© Ø¨Ø§Ù„Ù…ÙˆØ¶ÙˆØ¹ØŒ Ø®Ø§ØµØ© ÙƒØªØ§Ø¨ Ø·Ø±Ø§Ø¦Ù‚ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø© Ù…Ø¹ ØµØ§ØØ¨ Ø§Ù„ÙÙƒØ±Ø©. ÙˆØªÙ… ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙˆÙÙ‚ Ù†Ø¸Ø±ÙŠØ© Ù…ÙŠÙ„Ø³ ÙˆÙ‡ÙˆØ¨Ø±Ù…Ø§Ù† ÙˆØ³Ù„Ø¯Ø§Ù†Ø§. ÙˆØ£Ù…Ø§ Ù†ØªØ§Ø¦Ø¬ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« ÙÙ‡ÙŠ Ø£Ù† Ø§Ù„Ø·Ø±Ø§Ø¦Ù‚ Ù„ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØ© Ù„Ù„Ø·Ù„Ø¨Ø© Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠÙŠÙ† ÙˆÙÙ‚ Ø£ÙÙƒØ§Ø± Ø£ØÙ…Ø¯ ÙØ¤Ø§Ø¯ Ø£ÙÙ†Ø¯ÙŠ ØªØØªÙˆÙŠ Ø¹Ù„Ù‰ Ø«Ù„Ø§Ø«Ø© Ø£Ù…ÙˆØ± ÙˆÙ‡ÙŠ: (1) Ø¶Ø±ÙˆØ±Ø© Ø§Ù„Ø§Ø³ØªÙØ§Ø¯Ø© Ù…Ù† Ø·Ø±Ø§Ø¦Ù‚ ØªØ¯Ø±ÙŠØ³ Ø§Ù„Ù„ØºØ© Ø§Ù„Ù…Ø®ØªÙ„ÙØ©ØŒ ØÙŠØ« Ù„Ø§ ØªÙˆØ¬Ø¯ Ø·Ø±ÙŠÙ‚Ø© ÙˆØÙŠØ¯Ø© Ù…Ù†Ø§Ø³Ø¨Ø© Ù„Ø¬Ù…ÙŠØ¹ Ø§Ù„Ø¸Ø±ÙˆÙ ÙˆØ§Ù„Ù…ÙˆØ§Ù‚Ù. (2) ØªØ£ÙƒÙŠØ¯ Ø§Ù„Ø¬Ø§Ù†Ø¨ Ø§Ù„Ø§ØªØµØ§Ù„ÙŠ ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆØ°Ù„Ùƒ Ù„Ø£Ù† Ø£Ù‡Ù… Ø£Ù‡Ø¯Ø§Ù ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ø§ØªØµØ§Ù„. (3) ØªØ·Ø¨ÙŠÙ‚ Ø§Ù„Ø¯Ø±ÙˆØ³ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø§Ù„Ù…ÙƒØ«ÙØ© Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ù„ØºÙˆÙŠØ©ØŒ ØÙŠØ« ØªØªÙˆÙØ± ÙÙŠÙ‡ Ø§Ù„Ø³Ø§Ø¹Ø§Øª Ø§Ù„Ø¯Ø±Ø§Ø³ÙŠØ© Ø§Ù„ÙƒØ§ÙÙŠØ©. ÙˆØ®Ù„Ø§ØµØ© Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø¯Ù„Øª Ø¹Ù„Ù‰ Ø£Ù† Ø¥ØªÙ‚Ø§Ù† Ø§Ù„Ù…Ù‡Ø§Ø±Ø§Øª Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØ© ÙŠÙ…ÙƒÙ†Ù‡ Ø§Ù„Ø§Ø³ØªÙØ§Ø¯Ø© Ù…Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø·Ø±Ø§Ø¦Ù‚ Ø§Ù„Ù…Ø®ØªÙ„ÙØ© ÙˆØ§Ù„Ø§Ù‡ØªÙ…Ø§Ù… Ø¨Ø§Ù„Ø§ØªØ¬Ø§Ù‡ Ø§Ù„Ø§ØªØµØ§Ù„ÙŠ ÙˆØ§Ù„ØªÙƒØ«ÙŠÙÙŠ. Ø§Ù„ÙƒÙ„Ù…Ø§Øª Ø§Ù„Ù…ÙØªØ§ØÙŠØ©: Ø·Ø±Ø§Ø¦Ù‚ØŒ ØªÙ†Ù…ÙŠØ© Ø§Ù„Ù…Ù‡Ø§Ø±Ø§ØªØŒ Ø§Ù„Ø§ØªØµØ§Ù„ÙŠØŒ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù…ÙƒØ«Ù